DNA damage checkpoint execution and the rules of its disengagement - Yam, Candice Qiu Xia; Lim, Hong Hwa; Surana, Uttam (Frontiers in Cell and Developmental Biology, 2022)
Chromosomes are susceptible to damage during their duplication and segregation or when exposed to genotoxic stresses. Left uncorrected, these lesions can result in genomic instability, leading to cells’ diminished fitness, unbridled proliferation or death. To prevent such fates, checkpoint controls transiently halt cell cycle progression to allow time for the implementation of corrective measures. Prominent among these is the DNA damage checkpoint which operates at G2/M transition to ensure that cells with damaged chromosomes do not enter the mitotic phase. The execution and maintenance of cell cycle arrest are essential aspects of G2/M checkpoint and have been studied in detail. Equally critical is cells’ ability to switch-off the checkpoint controls after a successful completion of corrective actions and to recommence cell cycle progression. Interestingly, when corrective measures fail, cells can mount an unusual cellular response, termed adaptation, where they escape checkpoint arrest and resume cell cycle progression with broken chromosomes at the cost of genome instability or even death. Here, we discuss the DNA damage checkpoint, the mitotic networks it inhibits to prevent segregation of damaged chromosomes and the strategies cells employ to extinguish the checkpoint controls to override the G2/M arrest.